Late Ordovician deglaciation of the Murzuq Basin (SW Libya): a core to seismic-scale characterization of the depositional environments and sedimentary architecture. (December 2021) - Bataller, F.J.; McDougall, N.D.; Moscariello, A.; Gil-Ortiz, M.; Cavalcanti de Paula, B.
Abstract: Glacial reservoirs have been the focus of numerous studies in various basins around the world, often with the aim of supporting hydrocarbon exploration and development. These reservoirs present a significant challenge due to their inherently complex internal architectures and significant lateral heterogeneities. This is of significant importance, not only for both exploration and reservoir production optimization, but also as an opportunity for stratigraphic trapping and enhanced prospectivity in mature areas. This study is focused on a major glaciogenic reservoir, of Late Ordovician age, in the Murzuq Basin (SW Libya). It aims to integrate subsurface datasets, such as 3D seismic with well-based sedimentological data (core, conventional wireline logs and wellbore resistivity images). The study proposes a comprehensive facies scheme optimized for the sub-surface but consistent with outcrops, and aims to generate depositional models, characterize the complex internal architecture of the reservoir, establish a genetic stratigraphic framework and evaluate facies in terms of reservoir properties and stratigraphic trap potential. Results, integrating subsurface facies analysis and well-calibrated seismic stratigraphy support previous models, derived from outcrop analysis, suggesting that these complex reservoirs cannot be characterised by purely lithostratigraphic criteria. To aid in the assessment of these formations, a facies scheme is proposed, focused on subsurface data but also considering other published, outcrop-based, schemes. Additionally, an interpretation is presented of the internal architecture of the Upper Ordovician based on a succession of several ice advance-retreat cycles, not all of which are present across the study area. Each cycle corresponds to a seismic package interpreted to comprise the deposits of several key sedimentation phases, resulting in a complex mosaic of genetic packages generated by multiple, often areally-restricted, cut and fill events. Predictive stratigraphic models are proposed for this complex package, based on both seismic stratigraphy and well-based sedimentology. The implications for future prospectivity and the significance for stratigraphic trap potential are also discussed. Highlights: High resolution sedimentological and 3D seismic data integration study about Late Ordovician glacial sediments. Results show a complex architecture of these Late Ordovician glacial sediments which can lead to erroneous correlations. Results show a depositional pattern of low, high and low sediment supply phases related to ice advance and retreat stages Core data show that low sediment supply facies have enhanced reservoirproperties than the high sediment supply ones.